VD_FINDINFO Jug / 2023 / 309 vom 21. Februar 2023 - VD Tribunal cantonal (2023)
ESCROQUERIE, PERCEPTION ABUSIVE DE PRESTATIONS DE L'AIDE SOCIALE, PARTIE CIVILE, FIXATION DE LA PEINE | 146 al. 1 CP, 46 CP, 47 al. 1 CP, 49 al. 1 CP, 49 al. 2 CP